2015
DOI: 10.7150/jca.11404
|View full text |Cite
|
Sign up to set email alerts
|

High EGFR_1 Inside-Out Activated Inflammation-Induced Motility through SLC2A1-CCNB2-HMMR-KIF11-NUSAP1-PRC1-UBE2C

Abstract: 48 different Pearson mutual-positive-correlation epidermal growth factor receptor (EGFR_1)-activatory molecular feedback, up- and down-stream network was constructed from 171 overlapping of 366 GRNInfer and 223 Pearson under EGFR_1 CC ≥0.25 in high lung adenocarcinoma compared with low human normal adjacent tissues. Our identified EGFR_1 inside-out upstream activated molecular network showed SLC2A1 (solute carrier family 2 (facilitated glucose transporter) member 1), CCNB2 (cyclin B2), HMMR (hyaluronan-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Interestingly, the expression of MELK highly correlates with cell cycle genes AURKB , CCNB2 , TOP2A , and UBE2C , which are upregulated in high-grade PC ( Kuner et al , 2013 ) and appear to form a transcriptional network whose expression requires ING3 ( Figure 3A ), suggesting that ING3 regulates this pathway. Similarly, the expression of several genes from the EGFR inside-out pathway ( CCNB2 - HMMR - KIF11 - NUSAP1 - PRC1 - SLC2A1 - UBE2C ) ( Zhou et al , 2015 ) require the expression of ING3 ( Figure 3A ). The requirement of ING3 for the expression of these genes was validated by real-time qPCR ( Figures 3D–J ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the expression of MELK highly correlates with cell cycle genes AURKB , CCNB2 , TOP2A , and UBE2C , which are upregulated in high-grade PC ( Kuner et al , 2013 ) and appear to form a transcriptional network whose expression requires ING3 ( Figure 3A ), suggesting that ING3 regulates this pathway. Similarly, the expression of several genes from the EGFR inside-out pathway ( CCNB2 - HMMR - KIF11 - NUSAP1 - PRC1 - SLC2A1 - UBE2C ) ( Zhou et al , 2015 ) require the expression of ING3 ( Figure 3A ). The requirement of ING3 for the expression of these genes was validated by real-time qPCR ( Figures 3D–J ).…”
Section: Resultsmentioning
confidence: 99%
“…1 c) included the phosphatidylinositol 4,5-bisphosphate 3-kinase catalytic subunit beta isoform (PIK3CB) [ 41 ] and several members of the ubiquitin-proteasome pathway involved in development of inflammatory and autoimmune diseases [ 42 ]. For example, the ubiquitin conjugating enzyme E2-C (UBE2C), which activates several other genes (SLC2A1-CCNB2-HMMR-KIF11-NUSAP1-PRC1-UBE2C), triggering inflammation [ 43 ], and the UCHL5 (or ubiquitin C-terminal hydrolase UCH37), which plays an important role in inflammation and host defense [ 44 ]. Lastly, mRNAs enriched in MetS-EVs encode proteins involved in FGF signaling, a family of proteins which can contribute to pathological conditions by modulating expression of inflammatory cytokines [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin B2 (CCNB2), which belongs to B-type cyclins, is a cell cycle regulator [ 6 ]. A previous study indicated that CCNB2 was synthesized at G1 phase and quickly downregulated at anaphase [ 7 ]. During cell cycle, the defects of CCNB2 led to the failure of G2/M checkpoint and stimulated gene mutations and tumorigenesis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%